2021
DOI: 10.1177/07342829211002332
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Multidimensional Item Response Theory Approach in Validating the Dimensionality of the Positive Youth Development Scale

Abstract: Positive youth development has gained a lot of attention recently since it acts as a protective factor for several risk behaviors and other important life outcomes in adolescents and young adults. The main objective of this study was to explore the factorial structure of the Positive Youth Development Scale (PYDS) using multidimensional item response theory (MIRT). Three different models were examined: a unidimensional model, a multidimensional model with six distinct dimensions, and a multidimensional bifacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…To control for response bias (i.e., extreme response style, acquiescence, see Bolt & Johnson, 2009), developers of the Arabic version chose to reverse-code eight items. Validity studies have confirmed the factorial structure of the Arabic PYDS (Tsaousis et al, 2021). For the purposes of the present evaluation, the 8-item Caring domain was used that assesses a person's proclivity to be empathic and caring toward others (see Appendix B).…”
Section: Participantsmentioning
confidence: 88%
“…To control for response bias (i.e., extreme response style, acquiescence, see Bolt & Johnson, 2009), developers of the Arabic version chose to reverse-code eight items. Validity studies have confirmed the factorial structure of the Arabic PYDS (Tsaousis et al, 2021). For the purposes of the present evaluation, the 8-item Caring domain was used that assesses a person's proclivity to be empathic and caring toward others (see Appendix B).…”
Section: Participantsmentioning
confidence: 88%